Principal's Managerial Competence in Increasing Raudhatul Athfal Educational Institutions’ Productivity in Jambi Province - Harianto, Dodi; Syukri, Ahmad; Hakim, Lukman (Journal of Social Work and Science Education, 2023)
This study aims to describe and analyze school principals’ managerial competence in increasing the productivity of Raudhatul Athfal educational institutions in Jambi Province, beginning with program planning, organization, implementation, monitoring, and evaluation. This is a field study with a qualitative approach. Techniques for gathering data include observation, documentation, and interviews. Data analysis employs an interactive model that includes data collection, data reduction, data presentation, and conclusion drawing. Validating data with persistence of observation and data triangulation. According to the findings of three RAs in Jambi Province, RA schools carry out the following activities: (1) Planning (Conceptual) school programs in one semester, such as meetings at the start of the semester to discuss vision and mission, program objectives, school self-reliance program selection, and other; (2) Organizing (Humanist) programs to increase RA’s productivity is accomplished by delegating tasks and functions to each teacher and RA education staff member. (3) Technical implementation (carrying out the planned programs) (4) technical supervision, supervision activities carried out by the head of the RA school, carried out informally every day and twice a week, and formally once a semester with visits to every locale.